Effects of High-Definition Transcranial Direct Current Stimulation Over the Left Fusiform Face Area on Face View Discrimination Depend on the Individual Baseline Performance - Wu, Di; Zhang, Pan; Liu, Na; Sun, Kewei; Xiao, Wei (Frontiers in Neuroscience, 2021)
A basic human visual function is to identify objects from different viewpoints. Typically, the ability to discriminate face view based on in-depth orientation is necessary in daily life. Early neuroimaging studies have identified the involvement of the left fusiform face area (FFA) and the left superior temporal sulcus (STS) in face view discrimination, but there remains controversy over whether one specific region, i.e., the FFA or STS, or both are important. Thus, this research examined the influence of high-definition transcranial direct current stimulation (HD-tDCS) over the left FFA or left STS on face view discrimination in two studies. In experiment 1, eighteen subjects performed a face view discrimination task before and immediately, 10 min and 20 min after anodal, cathodal and sham HD-tDCS (20 min, 1.5 mA) over the left FFA in three sessions. Compared with sham stimulation, anodal or cathodal stimulation had no effects that were detected at the group level. However, the analyses at the individual level showed that the baseline performance negatively correlated with the degree of change after anodal tDCS, suggesting a dependence of the change amount on the initial performance. Specifically, tDCS decreased performance in the subjects with better baseline performance but increased performance in those with poorer baseline performance. In experiment 2, the same experimental protocol was used except that the stimulation site was the left STS. Neither anodal nor cathodal tDCS over the left STS influenced face view discrimination in group- or individual-level analyses. These results not only indicated the importance of left FFA in face view discrimination but also demonstrated that individual initial performance should be taken into consideration in future research and practical applications.